2016
DOI: 10.3390/toxins8070228
|View full text |Cite
|
Sign up to set email alerts
|

Type II Toxin–Antitoxin Systems in the Unicellular Cyanobacterium Synechocystis sp. PCC 6803

Abstract: Bacterial toxin–antitoxin (TA) systems are genetic elements, which are encoded by plasmid as well as chromosomal loci. They mediate plasmid and genomic island maintenance through post-segregational killing mechanisms but may also have milder effects, acting as mobile stress response systems that help certain cells of a population in persisting adverse growth conditions. Very few cyanobacterial TA system have been characterized thus far. In this work, we focus on the cyanobacterium Synechocystis 6803, a widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 70 publications
0
19
0
1
Order By: Relevance
“…In the case of Type II TA systems, both of these components are small proteins (Schuster & Bertram, 2013). Previously, 69 Type II TA systems were predicted for Synechocystis (Kopfmann et al, 2016). While the majority of these proteins are plasmid-localized, consistent with their function in plasmid maintenance, 22 predicted TA systems are encoded in the main chromosome.…”
Section: Smaller Complexes and Protein-protein Interactions In Toxin-mentioning
confidence: 99%
“…In the case of Type II TA systems, both of these components are small proteins (Schuster & Bertram, 2013). Previously, 69 Type II TA systems were predicted for Synechocystis (Kopfmann et al, 2016). While the majority of these proteins are plasmid-localized, consistent with their function in plasmid maintenance, 22 predicted TA systems are encoded in the main chromosome.…”
Section: Smaller Complexes and Protein-protein Interactions In Toxin-mentioning
confidence: 99%
“…To inactivate functionally the TA systems [43] and facilitate plasmid loss, we constructed pRK3C, containing the three antitoxin genes from pPsv48C cloned in pRK415 ( Table 2), and introduced it into UPN827 to neutralise the three corresponding toxins.…”
Section: A Toxin-antitoxin System Prevents a Deletion In Ppsv48c Medimentioning
confidence: 99%
“…To evaluate the role of TA systems on plasmid maintenance, we proceeded to their functional inactivation, by supplying in trans the cognate antitoxins cloned in the broad-host range vector pRK415; resulting in the neutralization of the toxin by the cloned antitoxin, as described [43]. Antitoxin genes PSPSV_A0043, PSPSV_A0032 and PSPSV_A0020 from pPsv48A were amplified by PCR with their own promoters, cloned into pGEM-T Easy, excised as BamHI or NcoI-SacI (for PSPSV_A0032) fragments, and sequentially cloned into the BamHI, NcoI-SacI and BglII sites of vector pME6041, respectively.…”
Section: Inactivation Of Ta Systems and Estimation Of Deletion Frequementioning
confidence: 99%
“…Therefore, SigB‐activated long mRNA has a dual function by ensuring the repression of motility genes at both transcriptional and post‐transcriptional levels. Additional genomic configurations involving the overlapping of 5′ UTRs from genes with opposite or related functions have been described in several bacteria, indicating that the regulatory mechanism involving overlapping between the long 5′ UTRs of contiguous genes is widespread in bacteria (Cohen et al, ; Kopfmann, Roesch, & Hess, ; Lasa, Toledo‐Arana, & Gingeras, ; Wurtzel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SigBactivated long mRNA has a dual function by ensuring the repression of motility genes at both transcriptional and post-transcriptional levels. Additional genomic configurations involving the overlapping of 5′ UTRs from genes with opposite or related functions have been described in several bacteria, indicating that the regulatory mechanism involving overlapping between the long 5′ UTRs of contiguous genes is widespread in bacteria(Cohen et al, 2016;Kopfmann, Roesch, & Hess, 2016;Lasa, Toledo-Arana, & Gingeras, 2012;Wurtzel et al, 2012).The next breakthrough in the field came from the transcriptome analysis of another Gram-positive bacteria, Staphylococcus aureus, which demonstrated that overlapping RNA transcripts are digested genome-wide by the action of the double-stranded endoribonuclease RNase III(Lasa et al, 2011). High-resolution transcriptome mapping was performed by combining the analysis of the total RNA fraction and the RNA fraction shorter than 50 nt.This methodological innovation turned out to be extremely useful for identifying the regions of the genome where overlapping transcription was taking place.…”
mentioning
confidence: 99%